Previous-day hypohydration impairs skill performance in elite female field hockey players - MacLeod, H.; Sunderland, C. (Scandinavian Journal of Medicine & Science in Sports, 2012)
The purpose of this study was to determine the effects of 2% hypohydration on skill performance in elite female field hockey players following intermittent exercise in the heat. Eight elite female field hockey players performed 50 min of a field hockey-specific intermittent treadmill running protocol (FHITP) in hot environmental conditions (33 °C, 60% relative humidity) in different hydration states: euhydrated (EUH) and hypohydrated by 2% body mass (HYPO). Hydration status was manipulated via a period (121±10 min) of passive hyperthermia (40 °C, 75% relative humidity) and controlled fluid intake 1 day preceding testing. Ad libitum fluid intake was permitted throughout both trials. Field hockey skill tests were performed pre- and post-FHITP. Skill performance time increased (P=0.029) in the HYPO trial compared with the EUH trial, which may be attributed to an increase in penalty time (P=0.024). Decision-making time increased (P=0.008) in the HYPO trial and was significantly impaired compared with EUH (P=0.016) pre-FHITP. Ad libitum drinking appeared to be sufficient to maintain decision-making performance as no interaction effects were evident post-FHITP. Players who commence match-play in a state of hypohydration may be susceptible to decrements in skill and decision-making performance.